If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -1) = 2(4x + 5) Reorder the terms: 6(-1 + 2x) = 2(4x + 5) (-1 * 6 + 2x * 6) = 2(4x + 5) (-6 + 12x) = 2(4x + 5) Reorder the terms: -6 + 12x = 2(5 + 4x) -6 + 12x = (5 * 2 + 4x * 2) -6 + 12x = (10 + 8x) Solving -6 + 12x = 10 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -6 + 12x + -8x = 10 + 8x + -8x Combine like terms: 12x + -8x = 4x -6 + 4x = 10 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 + 4x = 10 + 0 -6 + 4x = 10 Add '6' to each side of the equation. -6 + 6 + 4x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 10 + 6 4x = 10 + 6 Combine like terms: 10 + 6 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 3x(y-1)-x^2(1-y)= | | -4g=1 | | -3=8-4P | | T(n)=5-2n | | -6k+7.3=8.5 | | 2(3x+4)=4x+20 | | 25=x+3 | | 13.6=4r-0.8 | | 8x^2+5x=0 | | -7x^2-3x=0 | | 13x+35-21-9x=-2x-4 | | 7.6+5r=8.4 | | 2q-4.9=13.2 | | 11-4f=-9 | | 5+3g=14 | | 49-3x=6x+18 | | -6(s+11)=-24 | | 4r-3=-15 | | 625a+25b+20=0 | | 45=x-27+5 | | 2x^2+3x-100=0 | | 4y+4x=40 | | x*x-12x+27=0 | | 30x=168 | | 6(w-1)=6 | | 6p+1=4p-5 | | 5m+2=3m+8 | | 2x+8x=0 | | (x+5)(x-3)+(x+7)(x-3)=0 | | 5m+4=4m+5 | | 10x-7y+3z+54=6 | | 8x-20=10x |